2016
DOI: 10.1016/j.jcorpfin.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Be nice to your innovators: Employee treatment and corporate innovation performance

Abstract: for their valuable comments. We also thank Xin Chang and Wenrui Zhang for sharing with us the non-executive stock option data. Po-Hsuan Hsu acknowledges the General Research Fund (GRF) sponsored by the Research Grants Council in Hong Kong (790913). All errors are our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 79 publications
8
89
0
Order By: Relevance
“…The large impact of human capital on product innovation found by Karlsson and Tavassoli (2016) is absent in rural, as well as urban, 15 results. Availability of employee benefits impacts rural innovation in an almost consistently positive manner, in line with the results of Chen et al (2016), with the largest point estimate associated with patented innovation. T A B L E 4 Results for baseline specification (S1)-rural and urban samples…”
Section: Dotzel and Faggiansupporting
confidence: 72%
“…The large impact of human capital on product innovation found by Karlsson and Tavassoli (2016) is absent in rural, as well as urban, 15 results. Availability of employee benefits impacts rural innovation in an almost consistently positive manner, in line with the results of Chen et al (2016), with the largest point estimate associated with patented innovation. T A B L E 4 Results for baseline specification (S1)-rural and urban samples…”
Section: Dotzel and Faggiansupporting
confidence: 72%
“…More recently, studies have found that employee-friendly practices influence corporate innovation performance. Chen, Chen, Hsu, and Podolski (2016) show that firms with better employee treatment policies generate more and better patents through improving employee satisfaction and teamwork. Similarly, document that firms with employee-friendly workplaces achieve greater innovative success.…”
Section: Employee-friendly Practicesmentioning
confidence: 99%
“…We then extend the database to all patents granted to 2014 using the Google Patent database in Chen et al. () and Gao et al. ().…”
mentioning
confidence: 99%
“…The combined database includes detailed patent information for patents granted by the USPTO from 1976 to 2010. We then extend the database to all patents granted to 2014 using the Google Patent database in Chen et al (2016) and Gao et al (2017). We employ an automated name-matching algorithm that matches the name and location of each patent assignee that appears in patents granted in 2011-2014 in the Google Patent database to a pool of names and locations that have appeared as assignees of patents listed in our merged database from 1976 to 2010.…”
mentioning
confidence: 99%